ANALISIS YURIDIS KEDUDUKAN HUKUM PENCANTUMAN NAMA AYAH DALAM AKTA KELAHIRAN ANAK LUAR KAWIN YANG DIAKUI PASCA PUTUSAN MK No. 46/PUU/VIII/2010 - NIM. A1011221304, YUNI SOPIA SINAGA (Jurnal Fatwa Hukum, 2025)
Abstract Constitutional Court Decision No. 46/PUU-VIII/2010 was a significant milestone in the development of family law in Indonesia, recognizing the existence of a civil relationship between an illegitimate child and their biological father, provided it can be scientifically and legally proven. This decision opened access for illegitimate children to civil rights, including recognition of their identity through the inclusion of the father's name on birth certificates. However, in practice, the implementation of this decision still faces various legal and administrative obstacles, particularly regarding the requirement for a court ruling and civil registration procedures. This article aims to analyze the legal status of including the father's name on birth certificates of illegitimate children following Constitutional Court Decision No. 46/PUU-VIII/2010 and examine its legal implications for legal certainty and the protection of children's rights. The research method used is normative legal research with both statutory and conceptual approaches. The results show that although the Constitutional Court decision has normatively recognized civil relationships, in practice, the inclusion of the father's name remains heavily dependent on court rulings and complex administrative mechanisms, potentially creating legal uncertainty and hindering the fulfillment of the child's best interests. Keywords: Children out of wedlock, Inclusion of Father's Name, Birth Certificate, Constitutional Court Decision. Abstrak Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 merupakan tonggak penting dalam perkembangan hukum keluarga di Indonesia karena mengakui adanya hubungan perdata antara anak luar kawin dan ayah biologisnya sepanjang dapat dibuktikan secara ilmiah dan hukum. Putusan ini membuka akses bagi anak luar kawin untuk memperoleh hak-hak keperdataan, termasuk pengakuan identitas melalui pencantuman nama ayah dalam akta kelahiran. Namun, dalam praktiknya, implementasi putusan tersebut masih menghadapi berbagai kendala yuridis dan administratif, khususnya terkait keharusan adanya penetapan pengadilan dan prosedur pencatatan sipil. Artikel ini bertujuan untuk menganalisis kedudukan hukum pencantuman nama ayah dalam akta kelahiran anak luar kawin pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 serta mengkaji implikasi hukumnya terhadap kepastian hukum dan perlindungan hak anak. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa meskipun secara normatif putusan Mahkamah Konstitusi telah memberikan pengakuan hubungan perdata, dalam praktik pencantuman nama ayah masih sangat bergantung pada penetapan pengadilan dan mekanisme administrasi yang kompleks, sehingga berpotensi menimbulkan ketidakpastian hukum dan menghambat pemenuhan kepentingan terbaik bagi anak. Kata Kunci: Anak Luar Kawin, Pencantuman Nama Ayah, Akta Kelahiran, Putusan MK.